Approval of non-schedule item for RCC bench & floor joints - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of approval of non-schedule item for RCC bench & floor joints of Brac University new campus project.